2022
DOI: 10.1186/s12884-022-04783-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality study in the Eastern Democratic Republic of the Congo

Abstract: Background The reduction of maternal mortality in developing countries such as the Democratic Republic of Congo (DRC) still raises many questions. Indeed, this large country in the heart of Africa ranks 4th among the eight countries that alone account for more than 50% of maternal deaths in the world, behind India, Nigeria and Pakistan. However, there is no up-to-date data on maternal mortality in eastern DRC. This study measures the mortality rate rate in health facilities in eastern DRC and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…We selected Kasongo HZ as the study site based on the results of a previous study on maternal mortality conducted in eastern DRC in three HZs—Kasongo, Kunda, and Kibombo—in southern Maniema Province. The previous study revealed that the Kasongo HZ had a higher maternal mortality rate, estimated at 698 deaths per 100,000 live births, than the other 2 HZs, which had 612 deaths per 100,000 live births in the Kunda HZ and 513 deaths per 100,000 live births in the Kibombo HZ [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected Kasongo HZ as the study site based on the results of a previous study on maternal mortality conducted in eastern DRC in three HZs—Kasongo, Kunda, and Kibombo—in southern Maniema Province. The previous study revealed that the Kasongo HZ had a higher maternal mortality rate, estimated at 698 deaths per 100,000 live births, than the other 2 HZs, which had 612 deaths per 100,000 live births in the Kunda HZ and 513 deaths per 100,000 live births in the Kibombo HZ [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the DRC, as per the maternal death notification system, >32% of maternal deaths in 2018 were related to delays in seeking obstetric care [ 17 ]. More recently, a 2021 study in the Maniema Province of eastern DRC estimated that the maternal mortality ratio was 620 deaths per 100,000 live births, with 46% of these deaths attributed to the first delay in decision-making by the pregnant woman or her family to visit the place of delivery during the first uterine contractions [ 18 ]. According to Nkamba et al [ 2 ], pregnant women’s lack of awareness about and poor understanding of the ODS and erroneous advice given by some healthcare providers during antenatal consultation (ANC) sessions can delay seeking emergency obstetric care, thereby increasing the risk of maternal deaths [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food taboos during pregnancy are a set of systematic rules about which foods or combinations should not be consumed because they harm the pregnant woman and fetus. 29 Pregnant women abstain from consuming foods that are the richest sources of iron, carbohydrates, animal protein, and micronutrients not only in Indonesia but also in Ethiopia, 35 Gambia, 36 Nigeria, 22 South Africa, 37 and the Democratic Republic of the Congo 38 because the baby may have bad habits after birth or may have a disease at birth. In addition, in several low- and middle-income countries in Asia, dietary restrictions also include restrictions on the quantity and quality of food consumed by pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Selon son étiologie, on évoque les causes mécaniques (filière génitale, foetus et annexes) et dynamiques (contraction utérines). Malgré les efforts fournis, pour l'OMS les accouchements dystociques sont responsables des proportions inquiétantes des décès maternels dans le monde [3], [5], [9] . Sur l'ensemble des pays en voie de développement, Kwast [10] estime qu'il y aurait approximativement 85.000 décès maternels par an imputables aux dystocies.…”
Section: Introductionunclassified